Sistema Basado en Conocimiento Mediante RNA para Pronosticar las Ventas del Restaurante Combiche en el Mall Aventura - López Andrade, Alex Michael André (2021)
Actually, the artificial intelligence is applied to multiple business activities_x000D_ from the area. Since automation to forecasting for decision making, the sales_x000D_ area in companies rely on computer technologies for storing information so that_x000D_ they can determine if they are increasing or decreasing in a certain time._x000D_ This information work provides a knowledge system based on Neural Networks_x000D_ that has from the information on sales that you have, can forecast the future of_x000D_ these. The knowledge-based system was designed to forecast sales using neural_x000D_ networks as the main tool._x000D_ I implement an application to access using a graphical interface that allows us_x000D_ to train our neural network and forecast future sales. It was concluded that the_x000D_ system manages to efficiently forecast sales at the Combiche restaurant in the_x000D_ Aventura Plaza Mall in Trujillo